2012
DOI: 10.1007/s00134-012-2596-y
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic aortic injury score (TRAINS): an easy and simple score for early detection of traumatic aortic injuries in major trauma patients with associated blunt chest trauma

Abstract: Given the relative infrequency of traumatic aortic injury, which often leads to missed or delayed diagnosis, application of our score has the potential to draw necessary clinical attention to the possibility of aortic injury, thus providing the chance of a prompt specific diagnostic and therapeutic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(47 reference statements)
1
15
0
5
Order By: Relevance
“…[8,11] Mosquera et al reported mean age to be 41.33 years, and 26.3% of patients were over 55 years of age. [12] Present study results correlated with literature findings. Rupture of the transected aorta in blunt thoracic trauma causes intrathoracic bleeding, which leads to resistant hypotension and a significant risk for mortality if not repaired in time.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…[8,11] Mosquera et al reported mean age to be 41.33 years, and 26.3% of patients were over 55 years of age. [12] Present study results correlated with literature findings. Rupture of the transected aorta in blunt thoracic trauma causes intrathoracic bleeding, which leads to resistant hypotension and a significant risk for mortality if not repaired in time.…”
Section: Discussionsupporting
confidence: 88%
“…Though not acutely lethal, these injuries may gradually lead to death. [5,12] In the present study, 4 cases had scapula fracture and 2 cases had sternum fracture. Subcutaneous emphysema may arise from direct trauma or esophageal and airway trauma.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations